The genus Rubus L.: An insight into phytochemicals and pharmacological studies of leaves from the most promising species - Reneta Gevrenova; Dimitrina Zheleva-Dimitrova; Vessela Balabanova (Pensoft Publishers, 2024)
Rubus L. species (Rosaceae) are traditionally used worldwide for their food and medicinal properties. Although raspberries and blackberries are well-known fruits, the leaves hold significant but often overlooked value. The review is focused on the phytochemicals and pharmacological studies on leaves from the most promising taxa. Through a comprehensive search of the MEDLINE, Scopus, and Web of Science databases, numerous research articles were identified. The studies revealed over 160 diterpenoids, triterpenoid acids, saponins, ellagitannins, phenolic and acylquinic acids, and flavonoids in the discussed Rubus species. These compounds contribute to the leaves' protective effects, including astringent, hypoglycemic, and wound healing activity. Moreover, Rubus leaves are used for relieving diarrhea as well as in the treatment of ulcerative colitis, owing to their anti-inflammatory and antioxidant properties. This review highlights R. sanctus, R. ibericus, and R. chingii, along with R. idaeus, as prospective raw materials for therapeutic applications.